Emergency Department Interventions and Their Effect on Delirium's Natural Course: The Folly May be in the Foley - Noel, Christopher B. (J Emerg Trauma Shock, 2019)
BACKGROUND: Delirium frequently affects older emergency department (ED) patients and has been associated with accelerated cognitive and functional decline, increased length of stay (LOS), and higher in- and out-of-hospital mortality. OBJECTIVES: Care provided in the ED may have downstream effects on delirium duration during hospitalization. This study aimed to identify the modifiable factors of ED care associated with delirium duration in patients admitted to the hospital through the ED. MATERIALS AND METHODS: This prospective cohort study enrolled ED patients who were 65 years and older and admitted to the hospital. Delirium was determined in the ED and during the first 7 days of hospitalization using the modified Brief Confusion Assessment Method. All delirious patients and a random selection (17%) of nondelirious patients were also enrolled. ED LOS, opioid administration, benzodiazepine administration, anticholinergic medication administration, and bladder catheter placement were obtained by medical record review. Multivariable proportional odds logistic regression was performed to determine if each of the factors was associated with delirium duration after adjusting for age, dementia, baseline function, comorbidity burden, severity of illness, nursing home residence, and central nervous system insult. RESULTS: A total of 228 patients were enrolled. ED bladder catheter placement was significantly associated (adjusted proportional odds ratio = 3.1, 95% confidence interval: 1.3 to 7.4) with increased delirium duration after adjusting for confounders. ED LOS, opioid administration, benzodiazepine administration, and anticholinergic burden, however, were not. CONCLUSIONS: ED bladder catheter placement was significantly associated with delirium duration and may present an opportunity for intervention.